Nacht vor Augen - Bertele, Brigitte; Stuttmann, Johanna, 1979-; Ruggaber, Jona; Koffler, Hanno, 1980-; Noir film GmbH & Co. KG; Eastwest Film Distribution GwBH ([Karlsruhe, Germany] : Noirfilm, 2008)
Twenty-five-year-old David returns from a Bundeswehr mission in Afghanistan to his home village in the Black Forest. His girlfriend Kirsten and his mother welcome him warmly and his shy eight-year-old brother is full of admiration for him. But David is close-mouthed, brusque, and not the same man he was before the mission. Shortly after his return, the Bundeswehr informally honours him for supposed heroism. He is said to have shot an Afghan assassin in self-defence, thereby saving the lives of his whole unit. David returns his old job as a paramedic and lives with Kirsten. But he can't sleep at night. Nightmares of Afghanistan plague him. David's life gradually goes out of control. --
Originally broacast as a motion picture in 2008.
Jona Ruggaber, Hanno Koffler, Petra Schmidt-Schaller.
Cinematographer, Mathias Prause; editor, Stephan Krumbiegel; music, Christian Biegai.
In German with optional English subtitles.
Winner of 1 Award of the Durban International Film Festival, in 2008: Best Actor (Hanno Koffler)
Winner of 1 First Steps Awards, Germany, in 2008: Feature Film
Keywords: Post-traumatic stress disorder -- Drama; Veterans -- Mental health -- Drama; Brothers -- Drama; Made-for-TV movies; Feature films; Internet videos; Streaming video